A memória músical de Geraldo Filme: os sambas e as micros-áfricas em São Paulo - Azevedo, Amailton Magno (2006)
This text intended to rebuild the samba composer Geraldo Filme´s musical memory and his relations with the black groups in São Paulo City. By analyzing and reflecting upon his memory, I concluded that Geraldo Filme and black groups elaborated what was called micro-áfricas , understood as cultural expressions of resistance to imprint their marks, projects, makings and knowledge in specific territories in town. Before a city impregnated by urbanization, metropolization and verticalization which the paulista elite transformed into a hegemonic project, the micro-áfricas appeared as a dissonant counter-point to the dominating cultural forms in order to operate other cities and other ways of living. By taking the analysis of Geraldo´s memory as a conducting line, the micro-áfricas were identified in his familiar and communitarian living, at the samba schools and samba circles, in his lyrics, musical instruments handcrafting, religiosity, dancing saloons, theater, shows, carnivals and in the rhythmic cycles of his musicality. These various living ways defined and delimitated the micro-africas as bothe public and private cultural expressions. When analyzed every living in its peculiarity and in the relation among themselves in the black territories, I rebuilt Geraldo Filme´s and micro-áfricas memory could and should be accessed constantly in the present so that the black groups cultural expressions may be preserved and re-signified